DAMPAK LITERASI DIGITALTERHADAP PELAYANAN PUBLIK DI INDONESIA DALAM PERSPEKTIF ETIKA - Amirulkamar, Said (TheJournalish: Social and Government, 2024)
Digital literacy refers to the ability to use and understand digital technologies effectively. It is essential for individuals to participate effectively in the digital world and contribute to improving the quality of public services. The purpose of the study is to analyze the impact of digital literacy on public services in Indonesia from an ethical perspective. Data sources were obtained from journals, official websites, online news, social media, and katadata. The analysis technique used content analysis. The results showed that public services in Indonesia are closely related to digital literacy. This is evidenced by four indicators that are part of the digital literacy development framework, namely digital skills, digital ethics, digital safety, and digital culture. Digital literacy in public services significantly changes various aspects and from an ethical perspective, focusing on the moral consequences and values associated with digital literacy. Digital literacy can be measured by indicators such as knowledge, skills and participation in the digital environment. Technological advancements do not create digital influence, and all parties have equal rights to digital services. Digital literacy can increase people's access to online services, improve the efficiency, accessibility and transparency of online services.